Effective Compliance Audit Model for Managing Process Safety in Process Industries - Edmund, Soon Boon Thiam (Universiti Teknologi PETRONAS, 2013)
US Occupational Safety and Health Administration (OSHA) developed a program called Process Safety Management (PSM) due to the increasing major accidents in the process industries which has resulted in the loss of life, pollution to the environment and also monetary and asset losses. The purpose of process safety management or commonly known as PSM is to prevent unwanted release of highly hazardous chemicals to reduce exposure to employees and other potential hazards to the environmental, property and other living organisms. The PSM program is being used in the US, Europe and other countries which have any related process industries such as Malaysia. PSM covers 14 elements which comply with the OSHA Act. One of the elements in discussion of this research is Compliance Audit. Compliance audit is a technique to verify that the implementation of the PSM program is in compliance with OSHA standards. Besides that, compliance audit is performed to determine potential weakness or deficiencies in the PSM program used. Thus, by performing compliance audit, the implementation of the PSM program can be improved and can reduce the potential occurrence of accidents while working. The main goal of the research is to develop a comprehensive and effective compliance audit model according to OSHA PSM Standards which includes the six essential components of a compliance audit; planning, staffing, format, conducting the audit, evaluation and corrective and documentation. Prior to development of model, a framework is drafted as a guidance.The compliance audit model is a computer database to capture data and analyse the data. The model utilizes the Piping and Instrumentation Diagram (P&ID) as a basis to conduct the audit. Case study based on Operating Procedure and Training elements is performed to verify the effectiveness and also to ensure model compliance with OSHA PSM standards. The implementation of the model in the near future can assist auditors to conduct a systematic and efficient work flow of the audit. The compliance audit model is also beneficial to the employee as the weaknesses in the PSM program can be identified and rectified to prevent any major accidents such as in Bhopal or Flixborough.